Effect of organic manures and bio fertilizers on growth, yield and economics of coriander - Donga, S.J.; Chovatia, P.K.; Verma, H.P.; Rupareliya, V.V. (Annals of Agricultural Research, 2017)
A field experiment was conducted during rabi season of 2012-13 on medium black calcareous soilunder South Saurastra Agro climatic Zone to study the effect of organic manures and bio fertilizerson growth and yield of coriander. Results revealed that application of recommended dose of fertilizer(20-10-0:N-P2O5-K2O) being statistically at par with application of vermicompost @ 1.0 t ha–1 andcaster cake @ 0.5 t ha–1. significantly increased the plant height (49.80 cm), dry weight (0.31 gplant–1), no. of branches plant–1 (6.67), plant spread (25 cm) seed yield (1430 kg ha–1) and straw yield(1523 kg ha–1). Inoculation with Azotobactor + PSB @ 10 ml kg–1, gave significantly higher plantheight (50.91), dry weight (0.29 g plant–1), no. of branches plant–1 (6.60), plant spread (23.21 cm) overno inoculation.